Termination of the Ganderian Cambrian–Ordovician Miramichi terrane in east-central Maine, northern Appalachian orogen, USA - Ludman, Allan; Whittaker, Amber T. H. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2023)
The Ganderian Cambrian–Ordovician Miramichi terrane narrows in east-central Maine and terminates at the junction of faults that separate it from the mostly Silurian Central Maine/Aroostook–Matapedia basin (CMAM) to the northwest and Fredericton trough to the southeast. The terrane was emergent after Middle Ordovician recumbent folding and shed sediment to both adjacent depocenters. Its boundary faults are the youngest deformation events and play important roles in its termination, but do not by themselves explain it. The presence of distinctive CMAM strata southeast of the northwest boundary fault indicates that the first step in developing the current relationships was an episode of hitherto unrecognized late Silurian eastward thrusting. In the northern (Danforth) segment of the terrane, intermediate facies CMAM strata were thrust onto their Miramichi source rocks. The thrust sheet was deformed by Acadian upright folds, then dissected by dip-slip offset along boundary and internal faults prior to intrusion of the 409 ± 2 Ma Skiff Lake pluton. Subsequent erosion isolated a remnant of the thrust sheet as the Dill Hill klippe, its allochthonous CMAM strata isolated among Miramichi rocks. The southern (Greenfield) segment experienced similar events, but current relationships are different and timing of the late-stage faults is not well constrained. Allochthonous CMAM strata may have overridden the Miramichi terrane completely, so that a remnant of distinctive CMAM strata is now exposed east of the Miramichi terrane in fault contact with rocks of the Fredericton trough. The entire Greenfield segment is interpreted as a fault block exposed within the thrust sheet.